MOLECULAR-GENETIC IDENTIFICATION OF CAUSAL AGENTS OF FUNGAL DISEASES ON POTATO AND TOMATO COLLECTED UNDER PRODUCTION STORAGE - Zhanybekova , Zh.T.; Imanbekova , M.; Aitkulova, A.M.; Zholdybayeva, E.V.; Rakhimbayeva, D.D.; Kakimzhanova , A.A. (Eurasian Journal of Applied Biotechnology, 2019)
The expansion of exports and imports of potato and tomato crops between countries contributes to the rapid spread of the most harmful species and strains of phytopathogenic fungi around the world. Due to it, the identification of phytopathogenic fungi is important for agriculture. Currently, molecular-genetic methods are considered as one of the modern and promising methods for the diagnosis and identification of plant diseases, which allow identifying microorganisms without any knowledge of its biological features. One of the recommended methods for identification and classification of taxa is the determination of the nucleotide sequence of nuclear ribosomal gene regions. 276 infected potato tubers and tomato fruits were used to identify phytopathogenic fungi isolates, which were collected from production storages. Molecular-genetic identification of microorganisms based on the analysis of the nucleotide sequences of the ITS region made it possible to taxonomically identify 102 isolates of phytopathogenic fungi that belong to 7 genera. It was revealed that the proportion of fungi, which belohg to the genera Fusarium (60%), Penicillium (15%) and Clonostachys (12%), Alternaria (9%) were dominated in the generic structure. The isolation frequency (Fr) and relative density (RD) of 7 generaphytopathogenic fungi were calculated according to the results of molecular-genetic identification.Isolation frequency (Fr)of fungi genera ranged from 0.3% to 22.1%. Relative density of fungi species ranged varied 0.9% to 59.8%. Thereby, molecular-genetic identification based on the analysis of the nucleotide sequence of the ITS region made it possible to perform identification of pathogens on potato and tomato under production storage.Also, fungi Clonostachys and Acrostalagmus genera were isolated, which are not pathogens of potato and tomato diseases.